Theoretical Aspects of the Information and Knowledge Engineering - Duran-San Martin, C (Institute of Electrical and Electronics Engineers Inc., 2016)
Deepens the theoretical issues related to the Information and Knowledge Engineering with emphasis on reflection about its importance in the field of scientific research and social contribution to the development of the country. The paper presents these theoretical concepts: Information Engineering as the creation process and systematization of a volume of value-added data to a particular business. The Knowledge Engineering as the organized information that will facilitate recovery, capturing and processing in the form of a specialized knowledge; and the Strategic Competitive Intelligence as the understanding of a lack in the knowledge of the phenomena, identification of trends, risk mapping and discovery of opportunities related to the decision-making process in organizations. A systematic literature review is the method used in this study. Concludes that the information engineering (IE) and the knowledge engineering (KE) are revolutionaries in terms of information management in modern organizations. Active in the process of analysing large volumes of information they will have the power to reduce the cost by understanding the strategic business planning, data and modelling of processes, regardless of technology which will guide decision-making in any type of business. © 2016 IEEE.